Fanniidae (Insecta, Diptera) from Beijing, China, with key and description of one new species - Zhang, Dong; Li, Wei; Zhang, Ming; Wang, Ming-Fu; Wang, Rong-Rong (Zootaxa, 2016)
The Family Fanniidae in Beijing, China, consisting of seventeen species, is reviewed. Seven species represent new records from this region, including two species that are newly recorded from mainland China. One new species (Fannia papei sp. nov.) collected from the mountainous regions of Beijing is described. Three species (F. carbonaria, F. dupla and F. hirticeps) are re-described to provide updated characters and extensive variation information, and a key to identify the known males from Beijing is also given.